A Comparative Review of the Statutory Periodic Building Inspection Implementation in the Klang Valley Region, Malaysia and Hong Kong, China - Sarkom, Yazid; Abdul Ghani, Mimi Zaleha; Muhamad Ariff, Nor Rima; Jalil, Mohd Khairul Anuar; Kenawy, Inji (International Journal of Sustainable Construction Engineering and Technology, 2023)
Government response to building calamities using certain approaches depends on the types of building failures. Such approaches are the Periodic Building Inspection (PBI) in Malaysia and the Mandatory Building Inspection Scheme (MBIS) in Hong Kong. Both statutory requirements are meant to maintain the safety and structural integrity of buildings, and MBIS is selected for comparison with PBI because of the many parallelisms between the applications of both laws. Since it was made a statutory requirement in 1994, studies have found that PBI implementation by various local authorities in the Klang Valley region, Malaysia was insufficient. Comparing both statutory requirements offer insight and understanding into the compliance issues and solutions, therefore, benefiting the PBI from the proposed improvements. To achieve the aforementioned goal, the following objectives are proposed: a) To compare both statutory periodic building inspections; b) To identify gaps and best practices in both statutory periodic building inspections; and c) To propose improvements for PBI implementation. This research involves data gathering and comparative reviews of prior studies on PBI and MBIS. The study’s outcomes suggest significant similarities in the challenges faced during the implementation of both statutory periodic inspections. These challenges encompass unclear legal procedures, insufficient government participation, and weak enforcement. Building owners in both localities also encounter hurdles related to financial limitations, gaining consensus from residents, and selecting suitable engineers. Hong Kong’s targeted inspection using a risk-based approach priority can be emulated by local authorities in Malaysia. Hong Kong’s approach of allowing other qualified professionals like registered architects and building surveyors to perform initial visual inspections could also be applied in Malaysia. KPKT should consider providing financial support to low cost building owners, similar to the initiatives of the Hong Kong Housing Society (HKHS) and Urban Renewal Authority (URA). Local authorities and KPKT need to refine their service delivery through improved inter-departmental collaboration and heightened engagement with building owners. Revisions to Act 133, mirroring enforcement methods in Hong Kong, would be beneficial. Additionally, efforts should be made to raise public awareness about the significance of conducting PBI.